Kecemasan Orang Tua dan Anak Usia Toddler yang Mengalami Hospitalisasi - Sri Herlina; Rika Harini; Ponirah Ponirah; Salama Thomasita Batubara; Puji Astuti (Journal of Telenursing (JOTING), 2023)
This research aims to identify the anxiety of parents and toddler-aged children who are hospitalized in the children's room. The method used was descriptive analytic with a population of all those accompanying children while being cared for and toddler-aged children who were cared for in the last three months (September, October, November), namely 153 people, and a sample of 60 respondents was obtained using purposive sampling techniques. The instrument for this research is the Hamilton Anxiety Rating Scale (HARS) questionnaire. The research results showed that the majority of parents experienced mild anxiety, 29 respondents (48.3%), and the majority of toddler-aged children experienced mild anxiety, 30 respondents (50%). The conclusion was that most parents and toddler-aged children experienced mild anxiety. Keywords: Toddler Age Children, Hospitalization, Anxiety, Parents